Maqāṣidī Interpretation of Environmental Verses as a Solution to the Ecological Crisis and Global Climate Change - Zulfikar Zulfikar; Herliana Setyaning Pramesti; Khairunnisa Radhwa Nazihah; Khoirul Harisin; Muhammad Naufal Zulfikar (Magister Ilmu Al-Qur'an dan Tafsir UINSU Medan, 2026)
The ecological crisis and global climate change have become multidimensional problems affecting human survival and environmental sustainability. Environmental destruction, including deforestation, pollution, excessive exploitation of natural resources, and increasing carbon emissions, reflects a moral and spiritual crisis in the relationship between humans and nature. This study aims to analyze environmental verses in the Qur’an through a maqāṣidī interpretation approach in order to formulate ecological values relevant to addressing the global environmental crisis. This research employs a qualitative library research method using a thematic interpretation (maudhu‘i) approach. Primary data were obtained from Qur’anic verses related to the environment, while secondary data were collected from classical and contemporary tafsir literature as well as scientific studies on ecology and climate change. The analysis was conducted through the maqāṣid al-syarī‘ah approach to uncover the universal objectives of the Qur’an in preserving environmental balance and sustainability. The findings reveal that the Qur’an positions humans as khalifah with ethical responsibilities to protect and preserve nature. The principles of hifẓ al-bi’ah, the prohibition of fasād fi al-arḍ, and the concept of balance (mīzān) constitute the primary foundations of Qur’anic ecological ethics. The maqāṣidī interpretation of environmental verses further emphasizes that environmental preservation is not merely a social obligation but also a religious and humanitarian responsibility on a global scale. Therefore, the maqāṣidī approach offers a contextual and relevant ecological paradigm of the Qur’an in responding to the contemporary climate crisis.